DESIGNATION OF GEOSITES- PROPOSALS FOR GEOPARKS IN GREECE - Theodosiou, Ir. (Bulletin of the Geological Society of Greece, 2010)
During the last three years, the research project: “Geosites, geoparks contribution to sustainable development” aiming at recording and designating geosites and potential geoparks, as a means to sustainable development, funded from the 3rd Community Support Framework (CSF) programme, is developing at the Institute of Geology and Mineral Exploration of Greece (IGME). The project, according to its objectives, is divided in the following five sub-projects: 1: Identification, characterization, evaluation of geosites 2: Compilation of a DataBase and a Geographic Information System (GIS) for the geosites, geotrails and potential geoparks in the country. 3: Planning of walking and motoring geotrails around the geosites, in combination with other attractions of biotic, archaeological and cultural interest. 4: Specifications of the geoparks’ studies and planning for interpretation, tourism, marketing, development, operation and management. Drafting of complete management proposals for selected areas, in view of their development into geoparks and of their participation in international networks. 5: Promotion of the project’s objectives and benefits in international, national level and the local community, businesses and institutions. Compilation of interpretative, marketing material for tourism purposes, and for the community awareness on geological heritage conservation. The whole project is based on the systematic inventory of the geosites and the compilation of a GISaided database for the geosites, geotrails and potential geoparks. The framework of the research materialization, the procedural steps, as well as the methodological approach for its accomplishment, will be presented in this paper, focussing mostly in the first sub-project methodology as Geosites registration is the base for the whole project. The geosites, geotrails, potential geoparks Registry compiled with this project will function as a source of information for various uses: national and international level public or private sector projects regarding planning and conservation of nature, education and tourism.